2020
DOI: 10.1039/c9fo01998g
|View full text |Cite
|
Sign up to set email alerts
|

α-Lactalbumin and chitosan core–shell nanoparticles: resveratrol loading, protection, and antioxidant activity

Abstract: Resveratrol (RES)-loaded protein–polysaccharide nanoparticles were fabricated through simple electrostatic interactions with oppositely charged α-lactalbumin (ALA) and chitosan (CHI) with a mass ratio of 5 : 1 without the addition of NaCl at pH 6.5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The ABTS free radical scavenging ability of zein, GA and EGCG-loaded complex nanoparticles were tested according to Liu et al [ 23 ]. Before the ABTS experiment, the freshly prepared samples were evenly divided into three parts, one was without any treatment, one was adjusted pH to 6.8, and one was heated in a water bath pot (60 °C) for 1 h. ABTS radical solution was obtained by mixing ABTS solution (7 mM) with potassium persulfate solution (4.9 mM) for 12 h in a dark environment.…”
Section: Methodsmentioning
confidence: 99%
“…The ABTS free radical scavenging ability of zein, GA and EGCG-loaded complex nanoparticles were tested according to Liu et al [ 23 ]. Before the ABTS experiment, the freshly prepared samples were evenly divided into three parts, one was without any treatment, one was adjusted pH to 6.8, and one was heated in a water bath pot (60 °C) for 1 h. ABTS radical solution was obtained by mixing ABTS solution (7 mM) with potassium persulfate solution (4.9 mM) for 12 h in a dark environment.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that 28/40 dual-frequency ultrasound effectively increased the encapsulation efficiency of resveratrol in zein–chitosan complex nanoparticles from 51% to 65% [ 142 ]. After encapsulation, resveratrol lost its crystalline structure and changed to the amorphous form in alginate/chitosan–zein nanoparticles and α-lactalbumin–chitosan nanoparticles [ 103 , 104 ]. The major driving forces between resveratrol and α-lactalbumin–chitosan nanoparticles include hydrophobic interaction and hydrogen bonding [ 103 ].…”
Section: Applications Of Protein–polysaccharide Complexes/conjugates ...mentioning
confidence: 99%
“…After encapsulation, resveratrol lost its crystalline structure and changed to the amorphous form in alginate/chitosan–zein nanoparticles and α-lactalbumin–chitosan nanoparticles [ 103 , 104 ]. The major driving forces between resveratrol and α-lactalbumin–chitosan nanoparticles include hydrophobic interaction and hydrogen bonding [ 103 ]. Light, heat, and storage stabilities of encapsulated resveratrol in core-shell nanoparticles were remarkably increased compared to those of free resveratrol.…”
Section: Applications Of Protein–polysaccharide Complexes/conjugates ...mentioning
confidence: 99%
See 2 more Smart Citations